Conductive polymer-based sensors - Esteves, Henrique A.; Gonçalves, Wellington B.; Teixeira, Wanderson S. R. [UNESP]; da Silva Pádua, Ana C.; Gruber, Jonas (Wiley, 2023)
This chapter presents the main conductive polymers used in sensors and the methods for their synthesis, both chemically and electrochemically. The techniques for forming thin films and their interaction with volatile analytes are described This principle of operation allows their application in gas sensors and electronic noses, based not only on conductive polymers but also on conductive composites and conductive gels involving polymers and biopolymers. Moreover, conductive polymer sensors for strain, pressure, and temperature measurements are presented. Finally, this chapter describes some applications of these types of sensors in the medical and biomedical fields.
Keywords: Conductive polymers; Electronic noses; Gas sensors; Pressure sensors; Sensors; Strain sensors; Temperature sensors